(untitled) (Medico Legal Update, 2021)
Background: The aim of this study was to evaluate the effectiveness of educational interventions based on Health Belief Models (HBM) on the adoption of cervical cancer screening and prevention behaviours in Indonesian women in a rural district. Method: This is a quasi-experimental study with pre-test and post-test design. The convenience sampling was used and a total of 100 women participated in this study. One hour educational intervention based on a health belief model including lectures, question and answer, group discussions and booklets on cervical cancer and cervical cancer screening provided to participants. The content of the session included basic information regarding cervical cancer facts, important early detection, recommended screening method, guidelines for Pap smear screening and the role of pap smears in early diagnosis of cervical cancer. As well as, pamphlets distributed to participants. Post-test test hold within six months after the end of the intervention. Results: The findings showed that the mean difference of the scores before and after health educational intervention about Pap smear and cervical cancer for all constructs (except; perceived susceptibility and severity were no changes) has increased significantly with P-value <0.001. Conclusion: Providing rigorous information to women about the risk of cervical cancer the benefits of early detection of cervical cancer and having regular Pap smear tests are crucial to increase the intention to undergo cervical cancer screening among women in a rural area.